THE INFLUENCE OF DIGITAL-BASED STUDENT MANAGEMENT ON THE DEVELOPMENT OF STUDENT INTERESTS AND TALENTS - Susilowati Susilowati; Diana Evawati; Yunus Karyanto; Rina Asmaul (Indonesian Journal of Education (INJOE), 2025)
This study aims to examine the effect of digital-based student management on the development of students' interests and talents through a literature review. Digitalisation in student management facilitates data management, accelerates communication between schools, students, and parents, and expands students' access to various self-development programmes. The results of the study indicate that the application of information technology in student management can improve administrative efficiency, monitoring transparency, and student participation in extracurricular activities. In addition, a data-driven approach enables schools to design more targeted and measurable interest and talent development programmes. However, challenges such as the digital divide and limited technological competence among educators still need to be addressed. Overall, digital-based student management has great potential to support the optimal development of students' interests and talents, provided that it is supported by continuous evaluation and collaboration among all relevant parties